The relative importance to life of cortex and medulla of the adrenal glands - Houssay, Bernardo Alberto (1923)
The following facts are definitely established: I, Double adrenalectomy is fatal in most species, amongst them the dog. 2, Removal of all chromophil tissue contained in these glands is perfectly harmless. 3, Extirpation of inter-renal body (equivalent of cortex in Elasmobranchs) is followed by death. We may therefore conclude, I, The cortex is indispensable to life; it maintains its vital functions without the cooperation of the medulla. 2, The chromophil tissue of the suprarenals is not necessary to life or to normal functions. This does not mean that chromophil tissue is not indispensable to life. In our experiments only a part of this tissue is removed, and it must be remembered that relatively a greater portion of medullary tissue than of cortical tissue remains in the body after adrenalectomy. If chromophil tissue has vital functions, the extra-capsular portion is sufficient to maintain them, but up to now we have no evidence that these vital functions exist.